TumTá and Pisada: Digital Dance and Music Instruments Inspired by Popular Brazilian Traditions (Per Musi, 2021)
This paper presents the development process of TumTá, a wearable Digital Dance and Music Instrument that triggers sound samples from foot stomps and Pisada, a dance-enabled MIDI pedalboard. It was developed between 2012 and 2017 for the use of Helder Vasconcelos, a dancer and musician formed by the traditions of Cavalo Marinho and Maracatu Rural from Pernambuco, Brazil. The design of this instrument was inspired by traditional instruments like the Zabumba and by the gestural vocabulary from Cavalo Marinho, to make music and dance at the same time. The development process of this instrument is described in the three prototyping phases conducted by three approaches: building blocks, artisanal, and digital fabrication. We analyze the process of designing digital technology inspired by Brazilian traditions, present the lessons learned, and discuss future works.